Structural performance and charring of loaded wood under fire. (1st February 2021) - Qin, Renyuan; Zhou, Ao; Chow, Cheuk Lun; Lau, Denvid
Highlights: The structural and charring behavior of wood under real fire exposure is characterized. Current fire design codes underestimate the charring rate of wood under fire exposure. Service load accelerates charring of wood structural elements under fire. The mechanism behind the service loading on the thermomechanical behavior of wood is proposed. Abstract: Wood has been widely used in construction and infrastructures due to its great environmental and economic benefits. However, wood structures are highly vulnerable to fire because of its flammability. The effect of unavoidable service load on the structural performance and charring characteristics of wood structures is still unclear, posing serious safety risk under fire hazard. In this study, the fire behavior of wood components under different service loads was experimentally evaluated. To assess the fire performance in detail, the structural response and charring characteristics, including charring depth and charring rate were provided and compared. The results highlight that service load can accelerate the charring rate and increase the charring depth, aggravating the thermal degradation of wood element under fire exposure. An influential mechanism of service loading condition on the fire behavior of wood is proposed and a more accurate approach to predict charring rate is recommended. The findings from this study can advance the understanding on structural behavior of wood under fire and contribute to the trustworthy charring predictions as well as to reliable fire design of wood structures.